A Spatial analysis of chickenpox in Chongqing, China, during 2015–2023 - Lin Yang; Jule Yang; Dechao Tian; Han Zhao; Jiang Long; Li Qi (Scientific Reports)
Abstract The disease burden of Chickenpox has gradually increased in Chongqing in recent years. This study aims to investigate the epidemiology and spatial clustering of chickenpox in Chongqing. Data on chickenpox cases during 2015–2023 in Chongqing were collected from the China Information System for Disease Control and Prevention. Descriptive analysis and flexible spatial scan statistic were used to summarize epidemiological and spatial clusters of chickenpox cases. A total of 247,071 cases of chickenpox and 1 death were reported in Chongqing from 2015 to 2023, with an average annual incidence of 88.3 per 100,000, and the highest incidence was 133.85 per 100,000 in 2019. The male-to-female ratio of cases was approximately 1.12. Two peak epidemic pattern was observed with one from April to July and the other from October to January of the following year, except for 2020. The population group aged 0–14 years and students comprised the high-incidence groups. Cases have been reported in all 39 districts (counties) of Chongqing, with an average annual incidence rate ranging from 27.90 per 100,000 to 149.78 per 100,000. The annual flexible spatial scan statistic showed that the most likely clusters included Jiangbei District, Nan’an District, Beibei District, Yubei District and Bishan District. The most likely cluster areas were predominantly located in the main urban area, but they have gradually shifted to counties in southeast and northeast Chongqing during2015-2023. The incidence spatially clustered in several high-risk clusters in the main urban area of Chongqing, as well as in the southeast and southwest regions. Children under the age of 14 and students were the high-risk groups.